Developing A Dialogic Digital Reading Learning Environment For Indonesian Literacy: Evidence From Annotation, Discussion, and Comprehension Traces - Nursaid Nursaid; Mohamad Hafrison; Muhammad Ismail Nasution; Bima Mhd Ghaluh (Institute of Multidisciplinary Research and Community Service, 2026)
Digital reading environments make students' reading processes more visible because they capture annotations, discussion posts, comprehension attempts, and activity logs. However, these traces are often reduced to participation totals rather than used to inform the design of reading pedagogy. This study developed and evaluated a dialogic digital reading learning environment for Indonesian literacy. Using a design-based mixed-methods approach, 100 undergraduate students engaged with genre-based Indonesian texts over six weeks through interactive annotation, threaded discussion, audio support, and comprehension practice. The dataset comprised 1,842 annotations, 1,126 discussion comments, pretest and posttest reading comprehension scores, platform activity logs, and 20 follow-up interviews. The learning environment was organized around five dialogic engagement dimensions: text-grounded noticing, inferential linking, evaluative stance, dialogic uptake, and metacognitive reflection. Coding showed strong interrater reliability (Cohen's kappa = .86). Reading comprehension increased from pretest (M = 69.84, SD = 9.18) to posttest (M = 83.72, SD = 7.64), t(99) = 15.99, p .001, with a repeated-measures effect size of dz = 1.60. Dialogic uptake and inferential linking were the strongest predictors of comprehension gain, and the regression model explained 65% of the variance. Interview findings indicated that annotations helped students locate textual difficulty, discussion threads supported peer-mediated interpretation, and comprehension tasks prompted students to return to the text rather than respond superficially. The study offers a pedagogical model for designing Indonesian digital reading environments as social, reflective, and evidence-informed learning spaces. Keywords: Digital reading, Dialogic engagement, Learning environment, Social annotation; Indonesian literacy.